HUBUNGAN END USER COMPUTING SATISFACTION (EUCS) DENGAN KEPUASAN PENGGUNA SISTEM VERIFIKASI PENDAFTARAN ONLINE DI RSUP DR SARDJITO YOGYAKARTA: Corellation Between End User Computing Satisfaction (EUCS) and User Satisfaction with the Online Registration Verification System at RSUP Dr Sardjito Yogyakarta - Sri Sugiarsi; Erna Adita Kusumawati; Siti Mukminatul Khuro (Indonesian Journal of Health Information Management, 2025)
Health care facilities need to change the manual system with a new, more adequate information system so that it can improve the quality of service (IBISA, 2010). Dr. Sardjito General Hospital has launched an online registration system followed by an online registration verification system. System development continues to be carried out but obstacles are still found that affect user satisfaction. The purpose of this study was to determine the relationship between End User Computing Satisfaction (EUCS) and user satisfaction with the online registration verification system at Dr. Sardjito General Hospital Yogyakarta. The type of research is observational analytic with a cross-sectional approach. The sampling technique used total sampling with a total of 41 officers. The research instrument used a questionnaire. Data analysis used the Chi Square Test. The results of the study are a description of the content dimension as many as 83% stated that the system is according to needs, the accuracy dimension as many as 78% stated that the system is accurate, the format dimension 66% stated that the system display is good, the ease of use dimension 61% stated that the system is easy to use. The chi square test on the SPSS statistical program shows p_value on the content dimension = 0.004, accuracy dimension = 0.001, format dimension = 0.006, ease of use dimension = 0.001, and timeliness dimension = 0.001. The conclusion of this study is a general description of user satisfaction with the online registration verification system is satisfied with a percentage of 66%. All dimensions in the EUCS have a relationship with user satisfaction. Research suggestions, hospitals should conduct further research on the description of the EUCS dimensions and user satisfaction because it has not reached 100% and periodic system evaluations need to be carried out to ensure smooth use of the system and minimize obstacles.